PENGGUNAAN METODE PEMBELAJARAN MAKE A- MATCH UNTUK MENINGKATKAN PEMAHAMAN BERBELANJA BAHAN MAKANAN SISWA KELAS VIII D di SMP NEGERI 1 TEMPURSARI-LUMAJANG - Binti Robiati Sholihah (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
The research aims to know determining the exten to which teaching method of Make A- Match affect students’ level of understanding on how to choose good food materials on grocery shopping chapter. The subjects of the research are grade VIIIth students at Junior High School 1 Tempursari, even semester academic year 2014/2015. This research uses action research with 3 cycles that consists of phases, they are; (1) Action Plan (2) Action Implementation, (3) Observation and (4) Reflection. Learning strategy used is Group Investigation learning method. The data collection uses observation sheet and also competency test result of learning activity or evaluation. Data analyzing technique uses Qualitative Discriptive Technique. The result of research shows that there is an increasing from the first cycle to the third cycle, that is the average value on beginning tests 65,14 the completenes 51,43%, first cycle the average value of learning result is 71,14 and mastery learning 71,43% the second cycle the average value of learning result reaches 83,72 and learning completeness reaches 82,86% while the third cycle results achieved is very satisfactory with an average value of learning result reaches 93,11 with mastery learning reaches 97,14%. So, it can be concluded that Make A-Match method can increase the student’s learning interest and result.